Pemanfaatan Digital Marketing Untuk Optimalisasi Pemasaran Produk UMKM Di Masa Pandemi Covid-19 (Desa Gesang Kecamatan Tempeh Kabupaten Lumajang) - Dita Indah Puspitasari; Hadziqul Abror (PEKAT: Jurnal Pengabdian Kepada Masyarakat, 2022)
Marketing is one of the activities to maintain the continuity of a business, aiming to develop the business that is run and obtain a profit from the sales. Online media marketing or commonly called digital marketing can be said as a solution for running a promising business today, especially during the covid 19 pandemic. This service activity was carried out for MSME cake production in Gesang village- Lumajang with the theme "Program for Entrepreneurial Empowerment of Community Affected by Covid -19". The purpose of this activity is to improve product quality and also optimize online marketing, so that it is hoped that MSMEs can adapt during this pandemic and continue to grow in the future. The activity is carried out with the preparation stage in the form of observing problems and potentials, as well as the implementation stage in the form of problem solving stages and conducting online marketing training. The results of online marketing can increase visits on social media from 31 to 50. Sales in August increased every week, namely 14; 13; 20; and 30 pieces were sold. Digital marketing has proven to be able to optimize marketing.